Researching and Teaching Scientology: Perception and Performance of a New Religion - Gregg, Stephen E. (Implicit religion, 2020)
The academic study of Scientology (most often meant to mean the Church of Scientology) is complicated by a problematical inherited discourse between media, academics (and their students) and the Church of Scientology. In this short reflection piece, it is argued that this discourse should be understood within a wider context of attitudes to the study of New Religions within the academy, and the impact of CoS engagement with mainstream media. Additionally, it is argued that the preconceptions of both students and CoS representatives reflect these discourses, which in-turn impact not only upon research and teaching about Scientology, but also upon public projections of religious identity by the CoS. Referencing recent frameworks of Lived/Represented/Reported Religion, the article suggests that the study of diverse and everyday Scientology may offer a fruitful approach to future scholarship.